On periodic-type solutions of systems of linear ordinary differential equations - I. Kiguradze (Abstract and Applied Analysis)
We establish nonimprovable, in a certain sense, sufficient conditions for the existence of a unique periodic-type solution for systems of linear ordinary differential equations.